Tutor intervention profile: reliability and validity. - De Grave WS; Dolmans DH; van der Vleuten CP (Medical Education, 1998)
An instrument has been developed to provide tutors with feedback about their performance in problem-based tutorial groups. This questionnaire consists of 33 statements reflecting the behaviour of the tutor in the tutorial group when students analyse the case and generate learning issues and the behaviour of the tutor when students report back to the tutorial group about their self-study. The statements are grouped on theoretical dimensions found in the literature about co-operative learning and problem-based learning. This study focuses on the validity and the reliability of this instrument. Confirmatory factor analysis showed that a four-factor model showed a weak fit, whereas each separate factor fitted the data reasonably well. The four factors are: (1) elaboration; (2) directing the learning process; (3) integration of knowledge and (4) stimulating interaction and individual accountability. These factors were strongly correlated with the overall judgement of the tutor at the end of the unit, so the concurrent validity of this instrument was high. Generalizability studies indicated that the rating scales provide reliable information with a sample size of student responses falling within the range of real tutorial group sizes. The results of this study show that the instrument for providing tutors with feedback is valid and reliable. This questionnaire can be used in staff development activities and also provides needs assessment for faculty development.